80.8k views
1 vote
Which of the following is the correct expansion of (y + 1)(y2 + 2y + 3)?

y3 + 3y2 + 5y + 3


y3 + y2 + y + 3


y3 + 6y2 + 5y + 9


y3 + 5y2 + 6y + 3

User Taha
by
6.3k points

2 Answers

3 votes

Answer:

y3 - 4 y2 + 2 y - 5

Explanation:

User Cerkiner
by
7.0k points
4 votes

Use distributive property:

(a + b)(c + d) = ac + ad + bc + bd

(y + 1)(y² + 2y + 3) = (y)(y²) + (y)(2y) + (y)(3) + (1)(y²) + (1)(2y) + (1)(3)

= y³ + 2y² + 3y + y² + 2y + 3 = y³ + (2y² + y²) + (3y + 2y) + 3

= y³ + 3y² + 5y + 3

User Iizno
by
5.5k points